1999
DOI: 10.1042/bj3400069
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid inhibition of human SP-A1 promoter activity in NCI-H441 cells

Abstract: Glucocorticoids have complex effects on human surfactant protein (SP) SP-A1 and SP-A2 gene expression that occur at both transcriptional and post-transcriptional levels. In the lung adenocarcinoma cell line NCI-H441, dexamethasone causes a dose-dependent decrease in total SP-A mRNA levels and inhibits SP-A gene transcription. In this study, a deletional analysis of the SP-A1 promoter was performed in order to identify cisacting elements that mediate dexamethasone responsiveness in NCI-H441 cells. The region k3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
23
1
2
Order By: Relevance
“…Whereas no effect of Dex or cAMP was observed on expression of TK:hGH, Dex caused a 50% inhibition of cAMP-induced SP-A Ϫ990 :TK:hGH expression (data not shown), suggesting that Dex inhibition is mediated through SP-A 5Ј-flanking sequences between Ϫ47 and Ϫ990 bp. These findings differ from those of Hoover and colleagues (25), who reported that a region between Ϫ32 and ϩ63 bp of the hSP-A1 gene mediates Dex repression of transcription.…”
Section: Dex Acting Through the Gr Inhibits Sp-contrasting
confidence: 56%
“…Whereas no effect of Dex or cAMP was observed on expression of TK:hGH, Dex caused a 50% inhibition of cAMP-induced SP-A Ϫ990 :TK:hGH expression (data not shown), suggesting that Dex inhibition is mediated through SP-A 5Ј-flanking sequences between Ϫ47 and Ϫ990 bp. These findings differ from those of Hoover and colleagues (25), who reported that a region between Ϫ32 and ϩ63 bp of the hSP-A1 gene mediates Dex repression of transcription.…”
Section: Dex Acting Through the Gr Inhibits Sp-contrasting
confidence: 56%
“…A feature of the hSPA promoter that additionally makes it potentially useful in gene therapy is that it has a region that enables glucocorticoid-mediated inhibition of transcription enabling the in vivo control of gene therapy by glucocorticoid drugs. Hoover et al (36) identified the region of the hSPA1 promoter between ϩ14 and ϩ59 that is repressed by glucocorticoid, and this region included two negative glucocorticoid responsive elements (Fig. 3B).…”
Section: Design Of Cancer-targeted Tissue-specific Promoter Systemmentioning
confidence: 99%
“…The glucocorticoid effect on human SP-A gene expression is complex because it may involve transcriptional and posttranscriptional events (8,27,28,43,52). In human fetal lung explants, GCs reduce SP-A gene expression in a time-and dose-dependent manner.…”
mentioning
confidence: 99%
“…It was suggested that this biphasic decay rate was a result of differential effects of Dex on SP-A1 and SP-A2 mRNA stabilities. In fact, the two SP-A genes have been shown to be differentially regulated by certain agents, including GCs (27,31,35,42,55), and certain SP-A alleles may be differentially regulated by Dex (26).…”
mentioning
confidence: 99%